Utilization of Continuous Positive Airway Pressure (CPAP) by Emergency Medical Services: Updated systematic review and meta-analysis: CPAP for out of Hospital Respiratory Distress - Dhakal, Roshan; Karki, Deeven; Ghimire, Sujha; Ali, Rubiya; Dawach, Samia; Iqbal, Asra; Farzaneh, Roohie; Rahsepar, Sara; Panahi, Maryam; Bagherian, Farhad; Rezvani Kakhki, Behrang; Acheshmeh, Zahra; et al. (Galen Medical Journal, 2023)
Background: While new studies are being published on the prehospital continuous positive airway pressure (CPAP) application in patients with respiratory failure with conflicting results, previous meta-analyses are showing the benefits of CPAP in the prehospital transfer of patients with respiratory distress. Before the clinical application of high-level evidence, updated pooled estimates are needed based on the growing literature. This study aimed to compare prehospital CPAP with the usual standard oxygen therapy of respiratory failure patients. Materials and Methods: PRISMA guidelines served as the framework for this updated review study. It is an extension of a prior systematic review. We conducted comprehensive searches across several databases, including PubMed, Web of Science, Embase, and Scopus, focusing on randomized trials that juxtaposed pre-hospital CPAP application against standard care. Our primary interest was to assess the in-hospital mortality risks, and we employed random effect models to aggregate risk ratios from the selected studies. Results: Four articles were gathered based on the review of the updated literature (2013 to November 2022) in conjunction with the research incorporated in the preceding meta-analysis with a total number of 747 patients receiving prehospital CPAP with 101 events of in-hospital mortality. In the standard treatment control groups, there were 713 patients and 115 deaths occurred. Pooled mortality risk comparison between the group of prehospital CPAP and standard care patients had no statistically significant difference (P=0.16). There was no heterogenicity. A regression between the year of the studies and the effect size showed increased RR in new studies (P=0.017). Conclusion: Still more randomized trials are needed with higher sample sizes to conclude the lifesaving efficacy of the out-of-hospital CPAP.